2017
DOI: 10.1111/head.13056
|View full text |Cite
|
Sign up to set email alerts
|

Which Matters More? A Retrospective Cohort Study of Headache Characteristics and Diagnosis Type in Soldiers with mTBI/Concussion

Abstract: Persistent post-traumatic headache is most likely to present with continuous pain. Migraine is the most common primary diagnosis type. The presence of a continuous headache was strongly associated with negative occupational outcomes. Primary headache diagnosis type was not. Headache characteristics, therefore, may be more important than diagnosis type when determining active duty status. Further prospective research is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…There are many questions and some controversy regarding the use of symptom profiles to classify or type PTH. 6 Furthermore, symptom profiles of patients with PTH are heterogeneous, and the profiles of multiple primary headache conditions appear to predominate concurrently in many of these individuals 7,8 and thus do not sit well or are not classifiable within existing primary diagnostic criteria. Should we classify these symptom profiles, as suggested by the ICHD, with respect to the primary headache syndromes?…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many questions and some controversy regarding the use of symptom profiles to classify or type PTH. 6 Furthermore, symptom profiles of patients with PTH are heterogeneous, and the profiles of multiple primary headache conditions appear to predominate concurrently in many of these individuals 7,8 and thus do not sit well or are not classifiable within existing primary diagnostic criteria. Should we classify these symptom profiles, as suggested by the ICHD, with respect to the primary headache syndromes?…”
Section: Introductionmentioning
confidence: 99%
“…12 Derek Denny-Brown described PTH in 200 consecutive head injury patients at Boston City Hospital in 1944. 7,8,[14][15][16][17][18] Some studies excluded subjects with mixed headaches. They were variable in severity and described as steady, throbbing, aching, dull, burning, or pressing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An evidence‐based review by Holtkamp, Grimes, and Ling also showed that post‐traumatic headache with features of migraine was the most frequently occurring symptom after mild traumatic brain injury. A recent retrospective study by Finkel et al found that 60% of their post‐traumatic headache cohort was consistent with migraine among the 166 distinct headache types identified. Service members in the U.S. military have also demonstrated a high prevalence of chronic, daily headaches after concussion usually resembling chronic migraine and strongly associated with co‐morbid post‐traumatic stress disorder (PTSD) …”
Section: Introductionmentioning
confidence: 99%